High variation in the response of calves to a low-dose lipopolysaccharide challenge is associated with early-life measurements - M.S. Gilbert; A. Lammers; W.J.J. Gerrits (JDS Communications, 2024)
Lipopolysaccharide (LPS) challenges are commonly used in animal studies as a model for infection with gram-negative bacteria and innate immune activation. We used a low-dose LPS challenge for evaluating interindividual variation in innate immune responses in calves. This was part of a larger study aimed at predicting interindividual variation in feed efficiency in veal calves by variation in feeding motivation, digestion, metabolism, immunology, and behavioral traits. However, due to unexpected high mortality, this LPS challenge was performed in 32 calves rather than in 130 calves, which was initially intended in that larger study, and the 32 calves subjected to the LPS challenge were removed from that larger study. The objective of this short communication is to report the effects of a low-dose LPS challenge in those 32 calves and to examine whether the high variation in calves' responses to LPS could be explained by parameters related to feeding motivation, digestion, behavior, and immunology measured in early life. Thirty-two male Holstein-Friesian calves of Dutch origin were intravenously injected with LPS (0.05 μg/kg of body weight) at an age of 72 ± 0.6 d. Rectal temperature and respiratory frequency were recorded before injection and every hour after injection up to 6 h. In the 8 wk before the LPS challenge, measurements were performed related to general health, feeding motivation, digestion, behavior, and immunity. Following LPS administration, 3 calves died of shock, a fourth calf was euthanized because of severe symptoms of shock and 3 other calves were treated with corticosteroids to counteract observed symptoms of shock. Within the group of 25 relatively mild-responding calves, large interindividual variation in clinical responses to LPS was observed. The maximum increase in rectal temperature varied from 0.6 to 1.9°C and averaged 1.2 ± 0.39°C (coefficient of variation was 32%). The maximum increase in respiratory frequency varied from 16 to 132 bouts/min and averaged 60 ± 28 bouts/min (coefficient of variation was 48%). Little differences were found in early-life measurements between the 7 heavy and 25 mild responders, although heavy responders tended to have a better umbilical hernia score, and had a lower score in a human approach test (i.e., were less reactive) and lower presence of fecal pathogens. The maximum increase in rectal temperature correlated negatively with blood hemoglobin concentration at arrival of the calves at the facilities (r = −0.59) and in wk 4 (r = −0.53). The maximum increase in respiratory frequency correlated negatively with fecal color score (r = −0.43) and positively with fur score in wk 5 (r = 0.50). Overall, mortality (12.5%) and variation in clinical response was high after a low-dose LPS challenge in clinically healthy calves and some hematological and health measurements in early life were related to the clinical response of calves to LPS.